2021
DOI: 10.1186/s13019-021-01720-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow reserve fraction: the optimal choice in lesion assessing and interventional guiding for patient with unstable angina pectoris and intermediate lesion wrapped with myocardial bridge: a case report

Abstract: Background It is difficult to choose correctly interventional strategy for coronary intermediate lesions combined with myocardial bridge. Endovascular imaging is advocated to guide treatment, but flow reserve fraction (FFR) is not recommended to guide the interventional treatment of myocardial bridge disease because of the inaccurate judgment misled by myocardial bridge. Case presentation In this study, we reported a case of a 56-year-old male pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Unstable angina is a complex cardiovascular disease associated with multiple causative factors [7]. Current studies suggest that the disease is caused by myocardial ischemia and hypoxia following the formation of a thrombus in the coronary arteries [8], but the exact etiology and pathogenesis remain to be further elucidated. Many studies have shown that some miRNAs and some of the genes they regulate may be diagnostic markers or therapeutic targets for unstable angina [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Unstable angina is a complex cardiovascular disease associated with multiple causative factors [7]. Current studies suggest that the disease is caused by myocardial ischemia and hypoxia following the formation of a thrombus in the coronary arteries [8], but the exact etiology and pathogenesis remain to be further elucidated. Many studies have shown that some miRNAs and some of the genes they regulate may be diagnostic markers or therapeutic targets for unstable angina [9,10].…”
Section: Introductionmentioning
confidence: 99%